Gold nanoparticle-loaded PEGylated dendrimers for theragnosis - Kojima, Chie; Cho, So-Hye; Higuchi, Eiji (SPRINGER, 2012)
Both therapy and diagnosis, theragnosis, are indispensable for personalized medicine. Gold nanoparticles (Au NPs) have photochemical properties and attenuate X-rays, which are useful for photothermal therapy and X-ray computed tomography (CT) imaging, respectively. Polyethylene glycol (PEG)-modified dendrimers (PEGylated dendrimers) have been used as drug carriers with prolonged blood circulation. In this study, Au NP-loaded PEGylated dendrimers were prepared as agents for photothermal therapy and CT imaging. Au NPs were grown in the PEGylated dendrimer by adding gold ions and reductants under various conditions to improve the properties. Both size and surface plasmon absorption of the Au NPs increased, dependent on the seeding growth conditions. Au NPs with near infrared absorption were also prepared by seeding growth from Au NP-loaded PEGylated dendrimers using formaldehyde. The Au NPs thus grown showed enhanced photothermogenic properties and CT intensities, enabling efficient photocytotoxicity and the enhancement of the blood pool in mice by CT imaging. Therefore, Au NP-loaded PEGylated dendrimers are a potential agent for theragnosis.
Keywords: RAY COMPUTED-TOMOGRAPHY; BIOMEDICAL APPLICATIONS; CONTRAST AGENT; POLY(AMIDOAMINE) DENDRIMERS; DRUG-DELIVERY; ATTENUATION; CATALYSIS; ABILITY; DESIGN; HEAT